Three-dimensional measurement of proximal radioulnar space during active forearm pronation - Matsuki, Keisuke; Sugaya, Hiroyuki; Takahashi, Norimasa; Tokai, Morihito; Ueda, Yusuke; Hoshika, Shota; Hamada, Hiroshige; Banks, Scott A. (Journal of biomechanics, 2020)
Distal biceps tendon ruptures have been reported to be associated with narrowing of the proximal radioulnar space. There have been no studies that three-dimensionally measured the distance between the bicipital tuberosity and the proximal ulna during active motion. The purpose of this study was to three-dimensionally measure the proximal radioulnar space during active forearm pronation in healthy subjects. Five healthy volunteers (10 forearms) were recruited for this study. They consisted of all males with a mean age of 37 years (range, 34–46 years). Lateral fluoroscopy of forearm rotation from maximum supination to maximum pronation was recorded for both forearms. Three-dimensional forearm kinematics were determined using model-image registration techniques with fluoroscopic images and CT-derived bone models, and the closest distance between the bicipital tuberosity and the proximal ulna was computed at each 30° increment of radial axial rotation relative to the distal humerus. The distance between the bicipital tuberosity and the proximal ulna decreased with pronation, reaching a minimum value at 90° of radial rotation (average 4.6 ± 1.3 mm), then increased with further rotation to maximum pronation (P = 0.004). The clearance between the proximal radioulnar space and the distal biceps tendon is very small (<1mm). Hypertrophy of the bicipital tuberosity or tendon can induce impingement and lead to tendon rupture.